Symposium 8: Research into Learning in Networked Outreach Initiatives: Symposium Introduction - Booth, Shirley (Proceedings of the International Conference on Networked Learning, 2006)
Universities and their staff are facing multiple new challenges as society offers them new roles as motors for development. They are taking on educational outreach tasks in greater numbers and with wider ambitions to shape the world we live in. Life-long learning, internationalisation, educational flexibility, diversity among target groups, trans-disciplinarity in courses and research efforts, competence development in the work-place and innovative use of information and communication technologies (ICT) are some of the issues that are of concern. And at the centre of these concerns is the shift from a focus on teacher in isolation in the academy to students in networks in society. The project we are presenting focuses on learning in situations where the university extends its boundaries beyond its traditional campus to offer various kinds of distance learning opportunities, in line with the outreach ambitions of the university. Networks of teachers and learners are linked across dimensions that were once taken for granted as fixed: time, place and culture. The three learning opportunities we have chosen are: IIIEE-YMP: The International Institute for Industrial Environmental Economics (IIIEE), based at Lund University, is running a series of Young Masters Distance Education Programs (YMP) for school students from all over the globe. The long-term goal is to develop a global understanding of the global issue of environmentally sustainable economic and industrial development, (http://www.ll.lu.se/research/lieu/IIIEEeng.htm). LUMA-GIS: The Centre for GIS (Geographical Information Systems) at Lund University offers a two year Masters programme (LUMA-GIS) for professionals and traditional students from all over the world, that is free of charge, mediated by internet, at a flexible pace, and optionally worked at individually or in groups. The programme is multidisciplinary; diverse and international, since the need for training is global; both theoretical and practical, involving mathematics and practice; and flexible, so that students can work where and when they need to, (http://www.ll.lu.se/research/lieu/GISeng.htm). Kommunal-RUHFS: At Lund University, a course has been designed for adults who are considering taking up studies at university, in collaboration with the largest Swedish trade union of local authority workers. It aims to introduce participants to the study forms and cultures of the university. The long-term goal is to raise the level of competence in the workplace, and prepare them for life-long learning, (http://www.ll.lu.se/research/lieu/RUHFSeng.htm). Features that these learning opportunities have clearly in common are flexibility of various kinds, diversity among participants, a challenge to earlier experience, and open learning in case-study, problem-based and project-oriented group work, all mediated in various ways through ICT. While learning as constitution of meaning is central, there are three features of learning we feel are especially important: the character of the constituted context for learning, temporal and spatial flexibility of opportunity for learning, and the meetings that take place in a diverse population of learners. The goals are therefore: to analyse and describe learning - in the sense of constituting meaning from a variety of experiences and potential paths - as it is found among the students of the courses we are studying; to analyse and describe the context for learning as it is experienced by individuals and groups when course participation engages with their personal educational histories and their current situations; to investigate the notions of flexibility and diversity as they are built in and assumed by the courses and the teachers, and as they influence the experienced context and learning; to bring the results of the individual studies together, to compare and contrast the learning afforded there, and to relate them to ICT-based educational initiatives in a wider sense; to turn the results to considerations of pedagogical design and support. The common research orientation is phenomenographic (Marton, 1981; Marton & Booth, 1997), extended to engage with specific issues as appropriate. Empirical studies are being carried out in which data is being collected that as closely as possible reflects the students' variations in ways in which the common attributes of flexibility, diversity and the constituted context for learning, are experienced by the groups of students engaged in the courses, as well as approaches to and outcomes of the learning process itself. The papers that are to be presented in this symposium are drawn from these studies, taking specific aspects of the research related to flexibility, diversity and the constitution of a context for learning when student meets students, teachers and learning activities. The research is financed by the Committee for Educational Science of the Swedish Research Council.